Gastric Outlet Obstruction sebagai Keluhan Awal Limfoma Gaster: Sebuah Laporan Kasus - Chen, Lie Khie; Mohammad, Nurhidayat; Rumondor, Bayu B; Muzellina, Virly Nanda (Jurnal Penyakit Dalam Indonesia, 2024)
Gastric lymphoma often presents with non-specific symptoms, contributing to delayed diagnosis. Gastric Outlet Obstruction (GOO) is a potential complication that may occur in patients with gastric lymphoma. A 62-year-old male patient presented with persistent weakness, nausea, and vomiting. His symptoms began with long-standing abdominal discomfort, which had not been further evaluated. Esophagogastroduodenoscopy (EGD) revealed GOO secondary to a mass, which, after pathological and immunohistochemical evaluation, was diagnosed as diffuse large B-cell lymphoma (DLBCL). The patient was subsequently given a nasojejunal feeding tube and treated with R-CHOP chemotherapy (rituximab, cyclophosphamide, doxorubicin, vincristine, and oral prednisone). The non-specific nature of gastric lymphoma symptoms often results in diagnostic delays, resulting in diagnoses at more advanced stages. Gastric lymphoma complicated by GOO poses distinct challenges, particularly in managing nutritional support, which can impair the patient’s performance status and, in turn, influence treatment response and overall survival. Due to the non-specific nature of initial symptoms, many patients with gastric lymphoma are diagnosed at later stages. Therefore, early screening for patients with atypical dyspepsia symptoms is essential to rule out malignancies, including gastric lymphoma.